History teaching: a class proposal in the perspective of inclusion (Research, Society and Development, 2019)
The present article consists of a reflection on the teaching of history in the perspective of inclusion. In this sense, the main purpose of this work is to present a suggestion of a lesson plan based on the teaching of inclusive history, in which all, disabled or not, are contemplated. In order to achieve this goal, a bibliographic review was elaborated based on Circe Bittencourt, Paulo Santos, Maria Ciavatta and other authors. It was concluded that the History teacher, in order to base his teaching practice on an inclusive approach, should value the students' protagonism, address human diversity as a fundamental element of the historical process, seek interdisciplinary dialogue, seek basic knowledge about disabilities and other aspects.